2020
DOI: 10.3390/s20143854
|View full text |Cite
|
Sign up to set email alerts
|

Performance Degradation Prediction Based on a Gaussian Mixture Model and Optimized Support Vector Regression for an Aviation Piston Pump

Abstract: Performance degradation prediction plays a key role in realizing aviation pump health management and condition-based maintenance. Thus, this paper proposes a new approach that combines a Gaussian mixture model (GMM) and optimized support vector regression (SVR) to predict aviation pumps’ degradation processes based on the pump outlet pressure signals. Different from other feature extraction methods in which the information of intrinsic mode functions (IMFs) is not fully utilized, some useful IMF compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In particular, Gaussian Mixture Models (GMM) have the capability of modelling complex multimodal probability distributions while maintaining a simple analytical description. GMMs are a popular approach in prognosis and have been used with success in applications such as fault diagnosis and performance degradation assessment of bearings by capturing the healthy data distribution [42], construction of degradation indices in aviation piston pumps [43] and condition monitoring of machine tool wear [44]. A similar approach will be followed in this work to characterize the probability distribution of the observed endurance tests.…”
Section: B Quasi-static Variationmentioning
confidence: 99%
“…In particular, Gaussian Mixture Models (GMM) have the capability of modelling complex multimodal probability distributions while maintaining a simple analytical description. GMMs are a popular approach in prognosis and have been used with success in applications such as fault diagnosis and performance degradation assessment of bearings by capturing the healthy data distribution [42], construction of degradation indices in aviation piston pumps [43] and condition monitoring of machine tool wear [44]. A similar approach will be followed in this work to characterize the probability distribution of the observed endurance tests.…”
Section: B Quasi-static Variationmentioning
confidence: 99%
“…The results showed that the proposed method can effectively identify the fault mode and has good accuracy [19]. In addition, he again proposed an SVR method using the Gaussian mixture model to predict the degradation process based on the pump outlet pressure signal, and compared with the existing methods, its prediction effect was better [20].…”
Section: Introductionmentioning
confidence: 97%
“…They used their approach to detect faults in a heating, ventilation, and air conditioning (HVAC) chiller system and validated the effectiveness of their approach in diagnosing single-source and multisource HVAC faults. Some useful EMD information of intrinsic model functions gathered with PCA and GMM for the pump's degradation was studied by [21]. Jianbo Yu [22] presented an adaptive GMM (AGMM) and employed Kullback-Leibler divergence (KLD) as an indicator for quantifying tool performance degradation.…”
Section: Introductionmentioning
confidence: 99%